Flood Risk Management Analysis in Sebha: A Study to Assess the Impacts and Strategies (Journal of Human Sciences, 2025)
This study aims to analyze flood risk management in the city of Sabha, located in southern Libya, through a comprehensive examination of available climatic data, including monthly and annual rainfall records, as well as topographic maps and satellite imagery that illustrate the distribution of natural terrain and internal valleys. These valleys are among the primary contributing factors to flooding, due to their sloping nature towards urban residential areas, leading to the accumulation of large volumes of water during periods of heavy rainfall. The study focuses on analyzing the relationship between rainfall distribution patterns and the natural drainage network within the city, and assesses the capacity of existing infrastructure to withstand such conditions, especially in light of the absence of an effective drainage system in many neighborhoods. The study also includes a detailed evaluation of current policies and procedures adopted by relevant authorities for flood risk management, such as response strategies and preventive planning, and examines their effectiveness in mitigating the negative impacts of flooding on residents and properties. Furthermore, the research analyzes the methods used in urban planning and the extent to which they incorporate climate risk considerations. It also assesses the presence and effectiveness of early warning systems and available rescue and relief mechanisms in terms of their availability, efficiency, and speed of activation when needed. Based on the analytical findings, the study concludes with a set of recommendations aimed at enhancing the city’s capacity to adapt to future climate-related risks, improving stormwater management strategies, and developing integrated monitoring and planning mechanisms to sustainably reduce the impact of floods.